Interleukin-22 Plays a Protective Role by Regulating the JAK2-STAT3 Pathway to Improve Inflammation, Oxidative Stress, and Neuronal Apoptosis following Cerebral Ischemia-Reperfusion Injury - Yongfei Dong; Chengyun Hu; Chunxia Huang; Jie Gao; Wanxiang Niu; Di Wang; Yang Wang; Chaoshi Niu (Mediators of Inflammation)
The interleukins (ILs) are a pluripotent cytokine family that have been reported to regulate ischemic stroke and cerebral ischemia/reperfusion (I/R) injury. IL-22 is a member of the IL-10 superfamily and plays important roles in tissue injury and repair. However, the effects of IL-22 on ischemic stroke and cerebral I/R injury remain unclear. In the current study, we provided direct evidence that IL-22 treatment decreased infarct size, neurological deficits, and brain water content in mice subjected to cerebral I/R injury. IL-22 treatment remarkably reduced the expression of inflammatory cytokines, including IL-1β, monocyte chemotactic protein- (MCP-) 1, and tumor necrosis factor- (TNF-) α, both in serum and the ischemic cerebral cortex. In addition, IL-22 treatment also decreased oxidative stress and neuronal apoptosis in mice after cerebral I/R injury. Moreover, IL-22 treatment significantly increased Janus tyrosine kinase (JAK) 2 and signal transducer and activator of transcription (STAT) 3 phosphorylation levels in mice and PC12 cells, and STAT3 knockdown abolished the IL-22-mediated neuroprotective function. These findings suggest that IL-22 might be exploited as a potential therapeutic agent for ischemic stroke and cerebral I/R injury.